Bottom-water temperature, oxygenation, and upwelling intensity of sediment core GeoB20911-1 - Portilho-Ramos, Rodrigo Costa; Hebbeln, Dierk; Hoogakker, Babette A A; Titschack, Jürgen; Wienberg, Claudia (PANGAEA, 2025)
This dataset presents the reconstruction of the oxygen minimum zone (OMZ) dynamics off the Angolan margin over the last glacial–interglacial cycle, based on sediment core GeoB20911-1. Bottom-water temperatures were reconstructed using Mg/Ca ratios measured in the deep-infaunal benthic foraminifera Globobulimina spp. Bottom-water oxygen concentrations were estimated from the carbon isotopic difference between epifaunal (Cibicidoides wuellerstorfi) and deep-infaunal (Globobulimina spp.) benthic foraminifera. Surface ocean productivity was inferred from the relative abundance of planktonic foraminifera species Globigerina bulloides, Neogloboquadrina dutertrei, Neogloboquadrina pachyderma (sinistral), and Neogloboquadrina incompta, which are typically associated with high-productivity upwelling systems. The age model for core GeoB20911-1 is based on the combination of five AMS radiocarbon dates on mixed planktonic foraminifera and the benthic δ¹⁸O record of Globobulimina spp.
Keywords: Angola margin; Angola oxygen minimum zone; Atlantic oxygen minimum zone; benthic foraminifera stable isotopes; Bottom water oxygen; Bottom water te; oxygen minimum zones; Planktonic foraminifera assemblage; South Atlantic Ocean; upwelling systems